PTH-130 A Comparison Of The Nutrition Screening Tool And Malnutrition Universal Screening Tool On Referral Rates For Dietetic Assessments. (9th June 2014) - Gopalakrishnan, K; Smith, H; Hewett, R; Poullis, A
Abstract : Introduction: We aimed to compare the "Nutrition Screening Tool" (NST) and the "Malnutrition Universal Screening Tool" (MUST) on referral rates for dietetic assessments in in-patients in a Tertiary Neurology and Neurosurgery unit. Each tool generates a score above which dietetic assessment is recommended (a NST a score of 12 or more out of 22, a MUST score of 2 or more out of 5). The MUST score is considered the gold standard assessment method. The NST has been introduced in some centres with anecdotal reports of a reduction in referrals for dietetic assessment. Methods: In-patients at the National Hospital for Neurology and Neurosurgery were assessed for a one month period. The NST and MUST was completed on all available in-patients. A comparison of the number of referrals to dieticians was made using each assessment tool. Results: 136 patients were screened. There were 77 women and 59 men. The age range was 18–89 years. The mean age was 52.4 years. For women the mean age was 49.7 years. For men the mean age was 56.0 years. There was a highly significant difference in the numbers referred to the dieticians. Using the NST scores, 3 out of 136 patients scored 12 or more (3 referrals (2%)). Using the MUST scores, 20 out of 136 patients scored 2 or more (20 referrals, (15%)) (P < 0.0001). The NST identified that 12 patients scored 8 or more. 7 of these had a MUST score of 2 or more. This means 58% of patients who score 8 or more using the NST would have been referred using the MUST. The NST identified that 13 patients scored 7 or more. 8 of these had a MUST score of 2 or more. This means 62% of patients who score 7 or more using the NST would have been referred using the MUST. The NST identified that 14 patients scored 6 or more. 9 of these had a MUST score of 2 or more. This means 64% of patients who score 6 or more using the NST would have been referred using the MUST. Conclusion: Using the NST results in a significantly lower number of referrals to dietitians compared to when nutritional assessment is made using the MUST score. This may be due to the NST score required for referral being too high. Therefore the NST needs to be revalidated using a lower referral score, possibly between 6 and 8. Further studies are required in order to ascertain the specific NST score appropriate for referral. Disclosure of Interest: None Declared.